A Family Quarrel: Azerbaijani Historians against Soviet Iranologists. Issue 5 (September 2015) - Yilmaz, Harun
Abstract : Azerbaijani national history theory poses a challenge to the conventional history writing of Iran. Since 1937, Azerbaijani Soviet historians in Baku have constructed an Azerbaijani national history and identity based on the territorial definition of the nation. This approach was supported by Joseph Stalin. By the 1940s, this narrative incorporated various components hitherto exclusively known as "Iranian, " such as the Medes. Meanwhile, Soviet Iranologists and Orientalists, followers of the conventional Iranian narrative, tried to avoid controversy with the Azerbaijani claims, which secured political support at the highest level. When Stalin died in 1953, the Iranologists raised their voices, which caused controversy with political connotations. Using primary source materials, this article sheds light on the first round of discussions between Azerbaijani historians, constructors of their national history, and the Soviet Iranologists, the proponents of conventional Iranian history. The article also shows the limits of the Communist Party's control over history writing and the hardships of accommodating contradictory interpretations of history within a multinational communist state.